2004
DOI: 10.1016/j.jvs.2004.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound findings after radiofrequency ablation of the great saphenous vein: Descriptive analysis

Abstract: Small vessel networks were detected adjacent to or in connection with most of the radiofrequency ablation-treated GSVs. SFJ ligation was associated with fewer small vessel networks and proximal GSV recanalization. Most below-knee untreated GSV segments remained patent, and most exhibited reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…[11][12][13] In one study, the incidence of these intrathrombus channels was 2.2% following RFA and 7.1% following EVLA. 11 It not known whether some of the larger AVFs examined in this review occurred as a result of the same process.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] In one study, the incidence of these intrathrombus channels was 2.2% following RFA and 7.1% following EVLA. 11 It not known whether some of the larger AVFs examined in this review occurred as a result of the same process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the reported follow-up periods for endovenous procedures were relatively short. 17 Our past experience and results of previous studies comparing the results of three different surgical techniques (complete stripping with HL, partial above-knee stripping with HL, and HL alone) have shown that the best recurrence rate, best improvement in CEAP class, and best event-free survival rates are achieved using complete stripping with HL. 18,19 The rate of residual reflux and recurrence after partial stripping can reach up to 20%, and this complication is found more often with patent belowknee saphenous veins than with IPVs undetected preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review comparing recurrence rates, overall complication rates, and symptom relief, it was found that surgery was not inferior to endovenous procedures. In addition, the reported follow‐up periods for endovenous procedures were relatively short 17 . Our past experience and results of previous studies comparing the results of three different surgical techniques (complete stripping with HL, partial above‐knee stripping with HL, and HL alone) have shown that the best recurrence rate, best improvement in CEAP class, and best event‐free survival rates are achieved using complete stripping with HL 18,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If there was an abnormal duplex ultrasound result (level 3-6), treatment was initiated and repeat duplex ultrasound was performed weekly until the thrombus retracted and stabilized at a level 2 to 3. 4 No further imaging was performed after this finding and discontinuation of anticoagulation.…”
Section: Methodsmentioning
confidence: 99%